Вы находитесь на странице: 1из 5

1

a2 b2 = (a b)(a + b)
(a b)2 = a2 2ab + b2
(a + b)2 = a2 + 2ab + b2
3

(a b) = a 3a b + 3ab b
3

(a + b + c) = a + b + c + 2ab + 2bc + 2ac


4

log 1 = 0

an
= a nm
m
a

log a a = 1

( ab )

a3 + b3 = (a + b)(a2 ab + b2)
2

a n a m = a m+n

m n

a b = (a b)(a + ab + b )
2

(a )

(a + b) = a + 3a b + 3ab + b
3

2 2

(a + b) = a + 4a b + 6a b + 4ab + b

(a + b)5 = a5 + 5a4b + 10a3b2 + 10a2b3 + 5ab4 + b5

= a mn

a b=

(
(
(
(

a b

)
b)
b)
b)

a b

a+

a
a+

(
a+b= (
ab=

= a b

a+ b

an
a
= n
b
b

a =1

= a + 3 a b + 3 ab + b

)(
b )(

a b

a +3

)
b )

a + ab + b
a 2 3 ab + 3

3.
:

sin + cos = 1
sin
a ) tg =
cos
cos
1
b) ctg =
=
sin tg
c) tg ctg = 1
1
a ) 1 + tg 2 =
cos 2
1
b) 1 + ctg 2 =
sin 2
1
a ) sec =
cos
2

a)

b)

a0

n m

an = a
n

, n

a = nm a

a k = nm a mk

ab = n a n b

a
=
b

log a x =

log b x
log b a

log a b =

1
log b a

log a b log b a = 1

a n = a,

x
log a = log a x log a y
y

a0

a = n a m , a > 0, m, n N

= a 3 a b + 3 ab b
3

1
ap

m
n

ap a p = 1

= a + 2 ab + b
3

= a 2 ab + b

)(

log a ( xy ) = log a x + log a y

ap =
:

log a N p = p log a N

log a k N =

1
log a N
k

a log a b = b
log 10 N = lg N
log e N = ln N

sin( + ) = sin cos + cos sin


sin( ) = sin cos cos sin
cos( + ) = cos cos sin sin
cos( ) = cos cos + sin sin
tg + tg
a ) tg ( + ) =
1 tg tg
tg tg
b) tg ( ) =
1 + tg tg
ctg ctg 1
a ) ctg ( + ) =
-0
ctg + ctg
ctg ctg + 1
b) ctg ( ) =
ctg ctg
1

30

45

60

00

2
3

3
4

5
6

120

135

150

90

sin

cos

tg

ctg

1
2

2
2

3
2
1
3
3

3
2
2 1
2 2
1

3
2
1
2

1
2

2
2

-1

-1

2
2

+

cos
2
2

+
sin sin = 2 sin
cos
2
2
+

cos + cos = 2 cos
cos
2
2
+

cos cos = 2 sin
sin
2
2
sin ( + )
sin ( )
tg + tg =
, tg tg =
sin + sin = 2 sin

cos cos

c tg + ctg =

7
6

180

210

0
-

3
2

-1

4
3

3
2

5
3

7
4

11
6

225

240

270
-1

300

315

330

2
2

2
2

2
1
2

1
2

5
4

4
:

sin 2 = 2 sin cos


a ) cos 2 = cos 2 sin 2
b) cos 2 = 1 2 sin 2
c ) cos 2 = 2 cos 2 1
2tg
ctg 2 1
tg 2 =
ctg 2 =
2
1 tg
2ctg

1 + cos 2
1 cos 2
b) sin 2 =
2
2
sin 2

1
+
cos

c) sin cos =
a ) cos 2 =
2
2
2

cos

sin
b) sin 2 =
c) sin cos =
2
2
2
2
2
a ) cos 2 =

3
-

2
2

3
2
1
3

2
2

-1

-1

360

1
2

= t ,
2

2tg
1 t2
2 = 2t ,
sin =
cos =
1+ t2
1+ t2
1 + tg 2
2
2t
1 t2
,
.
tg =
ctg

=
1 t2
2t

tg

5
:

cos cos

sin ( + )
sin ( )
, c tg ctg =
sin sin
sin sin

2
1
2

lim C = C
n

lim ( xn + y n ) = lim xn + lim y n


n

lim xn y n = lim xn lim y n


n

lim Cxn = C lim xn


n

lim

xn
xn lim
= n
y n lim y n
n

1
=0
n n

lim

C
C
= 0 lim p = 0, p > 0
n n
n n

lim

0, k < l

a x + a x + ... + ak 1 x + ak a0
lim 0 l 1 l 1
= , k = l
n b x + b x
+ ... + bl 1 x + bl
0
1
b0
, k > l
k

k 1

(U ) ' = nU U '
( a ) ' = a ln a U '
( e ) ' = e U '

sin t
sin t
sin t
1 lim
lim
=
=
t 0
t

0
t

0
t
t
sin t =

lim

n 1

0
0

(arcsin U )' =

(arccos U )' =

1U 2

1
1
lim1 + = e , lim (1 + U ) U = e
t
U 0
t

lim
t 0

( log a U ) ' =

log a (1 + t )
1
ln(1 + t )
=
a = e lim
=1
t

0
t
ln a
t

(ln U )' =

1
U'
U ln a

(arctgU )' =

1
U '
U

tgt
tgt
tgt
= 1 lim
= lim
=
t 0 t
t 0
t

0
t
tgt
arcsin t
arctgt
lim
= 1, lim
=1
t 0
t 0
t
t
lim
t 0

lim
t 0

( tgU ) ' =

at 1
et 1
= ln a a = e lim
=1
t 0
t
t

(1 + t ) 1 =
t

(chU )' = shU U '

1
U '
cos 2 U

( ctgU ) ' =

1
U '
1+U 2

( shU )' = chU U '

( cosU ) ' = sin U U '

lim

(thU )' =

1
U '
sin 2 U

1
U '
ch 2U

(cthU )' =

1
U '
sh 2U

( f [ u ( x ) ] ) ' = f ' (U ) U '

-
6
:

f ' ( x ) = lim

x 0

f ( x + x) f ( x )
x

C=0

(U v )' = U V ln U V ' + V U V 1 U '

y y 0 = f ' ( x0 ) ( x x0 )

(UV)=UV+UV

(UVW)=UVW+UVW+UVW

x x0 + f ' ( x0 ) ( y y 0 ) = 0

(U+V)=U V

(CU)=C(U)

lim
x a

0
0

f ( x)
f ' ( x)
lim
=
x

a
( x)
' ( x)

U U 'V UV '
:
'=
V2
V
7
:

( f ( x)dx ) ' = f ( x)
f ' ( x)dx = f ( x) + C
af ( x)dx = a f ( x)dx, a 0

f ( x)dx = F ( x) + C F ' ( x) = f ( x)

U '

1
U '
1+U 2

(arcctgU )' =

( sin U ) ' = cosU U '

U '

1U 2

( f ( x) g ( x)) dx = f ( x)dx + g ( x)dx

f ( x + b)dx = F ( x + b) + C
1
f (ax)dx = a F (ax) + C
1

f (ax + b)dx = a F (ax + b) + C

n
U dU =

dU

U n +1
+ C (n 1)
n +1

= ln U + C

a
a dU = ln a + C , (a > 0, a 1)
U
U
e dU = e + C
U

sin UdU = cos U + C


cosUdU = sin U + C
dU
cos U = tgU + C
2

dU

sn U
2

dU

sin U

= ctgU + C
= ln tg

U
+C
2

dU
U
cos U = ln tg 2 + 4 + C
dU
1
U
a 2 + U 2 = a arctg a + C

dU
1 U +a
=
ln
+C
2
2a U a
a U
dU
1 U a
b) 2
=
ln
+C
2
2a U + a
U a
dU
U
= arcsin + C
a
a2 U 2

a)

dU
U a
dU
2

UdV =UV VdU

-
b

f ( x)dx = F ( x) |

b
a

= F (b) F (a )

= ln U + U 2 a 2 + C

= ln U + U 2 + a 2 + C

U +a
shUdU = chU + C
2

chUdU = shU + C
dU
ch U = thU + C
2

dU

sh U = cthU + C
a ) tgUdU = ln cos U + C
b) ctgUdU = ln sin U + C
a ) ln UdU = U (ln U 1) + C
b) Ue dU = e (U 1) + C
2

8
( )

1
1
= 1 + y + y 2 + ... + y n + ... = y n , y < 1 ;
= 1 y + y 2 ... + (1) n y n + ... = (1) n y n , y < 1
1 y
1+ y
n =0
n =0

1
2
4
n 2n
=
1

y
+
y

...
+
(

1
)
y
+
...
=
(1) n y 2 n , y < 1

1+ y2
n =0

arctgy = y

y3 y5 y7
y 2 n+1
y 2 n+1
+

+ ... + (1) n
+ ... = (1) n
, y <1
3
5
7
2n + 1
2n + 1
n =0

ln(1 + y ) = y

y2 y3 y4
y n+1
y n +1
+

+ ... + (1) n
+ ... = (1) n
2
3
4
n +1
n +1
n =0

ln(1 y ) = y +

e y = 1+

y 2 y3 y 4
y n+1
y n+1

+
+ ... + (1) n
+ ... = (1) n +1
2
3
4
n +1
n +1
n=0

y y2
yn
yn
+
+ ... +
+ ... = , y R
1! 2!
n!
n =0 n!

sin y = y

y2
y 2n
y 2n
y3
y 2 n+1
y 2 n+1
+ ... + (1) n
+ ... = (1) n
, y R cos y = 1
+ ... + (1) n
+ ... = (1) n
, yR
3!
(2n + 1)!
(2n + 1)!
2!
(2n)!
(2n)!
n =0
n =0

(1 + y )

( 1)...( n + 1) n
( 1)...( n + 1) n
= 1 + y +
y + ... = 1 +
y , y < 1, R \ N
n!
n!
n =1